Evaluating different models of maternal stress on stress-responsive systems in prepubertal mice - Sheng, Julietta A.; Handa, Robert J.; Tobet, Stuart A. (Frontiers in Neuroscience, 2023)
Maternal adversity during pregnancy influences neurodevelopment in human and model animal offspring. Adversity can result from stressors coming from many different directions ranging from environmental to nutritional and physiological to immune (e.g., infection). Most stressors result in fetal overexposure to glucocorticoids that have been directly linked to long-and shortterm negative impacts on neurological health of offspring [1]. Neuropsychiatric diseases postulated to have fetal origins are diverse and include such things cardiovascular disease, obesity, affective disorders, and metabolic and immune disorders. The experiments in the current study compare 3 stressors: prenatal exposure to dexamethasone (DEX), maternal high fat diet (HFD) and maternal caloric restriction (CR). Offspring of mothers with these treatments were examined prepubertally to evaluate stress responsiveness and stress-related behaviors in in male and female mice. Prenatal exposure to synthetic glucocorticoid, DEX, resulted in decreased neonatal body weights, reduced social interaction behavior, and hypoactive stress response offspring exposed to maternal DEX. Maternal CR resulted in decreased body weights and social interaction behavior in males and females and increased anxiety-like behavior and acute stress response only in males. HFD resulted in altered body weight gain in both sex offspring with decreased anxiety-like behavior in a female-biased manner. The idea that glucocorticoid responses to different stressors might serve as a common stimulus across stress paradigms is insufficient, given that different modes of prenatal stress produced differential effects. Opposite nutritional stressors produced similar outcomes for anxiety-like behavior in both sexes, social-like behavior in females, and a hyperactive adrenal stress response in males.One common theme among the three models of maternal stress (DEX, CR, and HFD) was consistent data showing their role in activating the maternal and fetal immune response. By tuning in on the more immediate immunological aspect on the developing fetus (e.g., hormones, cytokines), additional studies may tease out more direct outcomes of maternal stress in rodents 55 and increase their translational value to human studies.